Finansowanie działalności inwestycyjnej przedsiębiorstw polskich z sektora MŚP w okresie integracji z Unią Europejską - Duda, Joanna ("Financing of Investment Activities in Polish Enterprises Belonging To SME Sector in the Period of EU Integration", 2007)
Polish access to the European Union caused many emotions, both positive and negative ones. Followers set their sight on the chances for development of Polish entrepreneurship, but entrepreneurs were afraid that their firms would go bankrupt on the common EU market because of the barriers limiting their access to outside financing sources. The above dilemmas induced the author of the paper to carry out the analysis of financing sources of small and medium enterprises' investment activities in the period of European integration.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1152, s. 115-123